S Wave Velocity Structure in Non-tectonic Indo-China by Analyzing the Earthquakes in Sumatra-Java in TATO Station, Taiwan - Santosa, Bagus Jaya (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2009)
The velocity structure of S wave under South-East Asia and South China Ocean due to earthquakes in Sumatra-Java subduction zone which data is recorded in TATO, Taiwan seismological station, has been investigated through seismogram analysis in time domain and three components simultaneously. The synthetic seismogram was calculated using GEMINI method, with the inputs are the earth model and the CMT solution of the earthquakes. A low-pas filter with corner frequency of 20 mHz was applied on the seismograms. Applying the deconvolution of unit response on the synthetic seismogram the seismogram comparison was executed in the same unit. The seismogram comparison indicated that the calculation from PREMAN synthetic seismogram deviates significantly from the measured ones. The deviation occurred on the arrival time of surface wave of Rayleigh and Love as well as S body waves. The interpretation results of seismogram analysis using waveform indicate that non-tectonic South-East Asia area in front of subduction zone has strong negative correction of ï¢v in the upper mantle and with smaller factor also at earth layers below. This result shows stronger vertical anisotropy than one in PREMAN earth model.